Feasibility Analysis Of Construction Of A Wall Factory Precast Concrete In Samarinda, East Kalimantan At PT. RA Beton - Oetomo, Dedy Setyo; Ramdhani, Rizky Fajar (Journal of Information System, Technology and Engineering, 2024)
The main objective of a business feasibility study is to assess opportunities for a business project and whether the project is worth continuing or not. Results of calculation analysis on PT RA Beton Precast Concrete Wall Product Manufacturing Plant Design with an average production capacity of 128,772 pcs/year with two product designs (Type A-A and Type B-B). Based on the cash flow of the development investment plan, the new factory PT. RA Beton requires capital of Rp. 169.866.126.151.The calculations using the four methods, namely payback period (PP), produce results of 2 years and 4 months less than the economic life or maximum payback period, which is 10 years. Next, using the net present value (NPV) method, the results obtained are the NPV1 value > 0 from 75% interest amounting to Rp. 5,111,998,649, and the NPV2 value < 0 from 80% interest amounting to -Rp. 5,826,301,054. In calculating the Internal Rate of Return (IRR), results were obtained with a value of 94% greater than the applicable interest rate, namely 12%. Each method produces a different value; calculating the payback period concludes that the investment proposal can be accepted and declared feasible because it meets the criteria.